Analisis Kebutuhan Pengembangan Media Pembelajaran Augmented Reality Pada Mata Pelajaran Informatika SMPN 8 Sungai Kakap - Nurbani Nurbani; Henny Puspitasari (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The background of the research is the lack of student learning independence and the absence of interesting learning media. To be able to learn independently, students need digital learning media to be used using Smartphones. In Augmented Reality media, there are not only text and images, students can also see objects in real images of a media. This study aims to determine the analysis of teacher and student needs for Augmented Reality-based learning media at SMPN 8 Sungai Kakap. To collect information using literature study and field study methods. Data analysis techniques used in this study used descriptive and percentage tests. The results of the study show that the analysis of student needs for the use of Augmented Reality-based learning media, especially in Informatics subjects at SMPN 8 Sungai Kakap assumes to develop AR-based learning media with a percentage of 93% in the analysis of the need for facilities for AR-based media. Analysis of student learning in Informatics subjects at SMPN 8 Sungai Kakap assumes 93% agreement seen from the analysis of learning style tendencies needs